Regional and Historical Minerageny of the Gemstone Complexes in Russia (Quantitative Aspects) - Polyanin V.S.; Polyanina T.A.; Dusmanov E.N.; Yakovleva E.I. (Учёные записки Казанского университета: Серия Естественные науки)
The paper presents an approximate quantitative estimation of the mineragenic potentials of gems in the paleogeodynamic systems, complexes, and geological formations of Russia, which are characterized by different age and regional distribution. General trends of the changes in the scale and intensity of formation processes of the same gem deposits over geologic time were identified.